1983
DOI: 10.1021/ja00357a016
|View full text |Cite
|
Sign up to set email alerts
|

The reactions of ethoxy radicals with optically active tertiary phosphines. Stereochemistry of the substitution process and the question of permutation modes for the possible phosphoranyl radical intermediates

Abstract: The reactions of (-)-(S)-2, MePhPCH2Ph, and (+)-(S)-3, zi-PrMePCH2Ph, with EtO• were shown to yield substitution products MePhPOEt and n-PrMePOEt, respectively. Both reactions occur with net inversion of configuration at phosphorus. The maximum optical yields, determined at very low phosphine conversions, were 96 ± 5% for (-)-(S)-2 and 78 ± 4% for (+)-(S)-3. Optical yields are very sensitive to reaction times and conversions, because the product phosphonites are readily racemized by EtOH formed during reaction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

1983
1983
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 4 publications
0
6
0
Order By: Relevance
“…For reaction of t-BuO • with ZP(OEt) 2 , R-cleavage predominates for Z ) PhCH 2 , t-Bu, Et, PhO, and Bu 2 N, whereas β-scission predominates for Z ) Ph and RO. 47 Overall inversion during substitution at P has been demonstrated 50 for several cyclic phosphites such as 44 and for phosphines such as 45.…”
Section: Stereochemistry Of Homolytic Substitutionsmentioning
confidence: 97%
See 1 more Smart Citation
“…For reaction of t-BuO • with ZP(OEt) 2 , R-cleavage predominates for Z ) PhCH 2 , t-Bu, Et, PhO, and Bu 2 N, whereas β-scission predominates for Z ) Ph and RO. 47 Overall inversion during substitution at P has been demonstrated 50 for several cyclic phosphites such as 44 and for phosphines such as 45.…”
Section: Stereochemistry Of Homolytic Substitutionsmentioning
confidence: 97%
“…However, it was inferred from the relative rates of alkyl radical loss that an M4 isomerization to 47, containing an apical alkyl ligand, preceded R-scission. 50,51 Equilibrium was established between 46 and a minor amount of isomer 47 from which loss of the apical alkyl group occurred. Firm experimental evidence is lacking about the direction of approach of attacking radical in the addition step.…”
Section: Stereochemistry Of Homolytic Substitutionsmentioning
confidence: 99%
“…This entropic effect makes the stability difference between the apical and equatorial isomers smaller for 6 than for 3 [ K ( 6 ) < K ( 3 )]. Bentrude38 and Roberts39, 40 have independently shown that the stereopermutation between ligands in apical and equatorial positions occurs by the M 4 mode41, 42 through intermediates of σ* geometry 43. The A factor, being lower than 10 13 s −1 , is indicative of strong steric hindrance in the transition state along the pathway to the intermediate of σ* geometry (Scheme ).…”
Section: Resultsmentioning
confidence: 99%
“…Reactions of R^rPCl with achiral alcohols in the presence of chiral tertiary amines such (+)-A^N-dimethyl-(l-phenylethyl)amine afford the expected chiral R ! Still another approach to chiral phosphinite esters is the reaction of alkoxy radicals with chiral tertiary phosphines (206). A second, more promising method to obtain chiral phosphinites is reaction of a chiral alcohol such as menthol (756) or cinchonine (24,25) with R'ArPCl to yield unequal amounts of the diastereomeric esters R !…”
Section: Cl"mentioning
confidence: 99%